Managing minor ailments and pharmacy services: How do people make their decisions? - Léa Charnaux; Jérôme Berger; Clémence Perraudin (PLoS ONE, 2025)
Background Healthcare systems face challenges such as rising costs and workforce shortages. Optimal resource allocation is needed, notably in the management of minor ailments. Community pharmacy services (e.g., minor ailment schemes) remain underused by the population. This study explores the decision-making process when people are managing minor ailments: What influences their choices among the management options? What is their level of information and willingness to use and pay for pharmacy services? Methods A cross-sectional online survey was conducted using a self-administered questionnaire (convenience sampling) from 07.11.2023 to 08.12.2023 in Switzerland. The survey explored general decision-making process in minor ailment management through three clinical scenarios, factors influencing the choice of pharmacy services, as well as public knowledge of three available pharmacy services and their willingness to use and pay for them. Results A total of 508 valid responses were analysed (99.8%). Perceived severity of symptoms (98%, n = 495) and time to deal with symptoms (78%, n = 396) were the most important criteria in making the management decision. The more serious the symptoms were perceived, the less the pharmacy and self-medication were privileged. Choosing pharmacy depended mainly on the perceived staff’s skills (83%, n = 420) and direct access to medicines (81%, n = 409). Public awareness of pharmacy services was low. Respondents were more willing to use autonomous prescribing than other services, with low willingness to pay out of their pocket. Conclusions There is a critical gap between the potential demand for minor ailment services in pharmacy and the public’s awareness and valuation of them. Actual uptakes could be improved by better communication and uniformization of pharmacy services, as well as the identification of right incentives to achieve the political goal of adequate orientation in the healthcare.